SIMULASI SISTEM PEGAS MASSA - Vitaloka, Dwi Candra; Hasan, Moh; Hidayat, Rusli (Department of Mathematics Education , University of Jember, 2013)
Abstract.Mass spring system is a system composed of objects that have mass and are connected by a spring. The series of spring can be composed of several pieces of spring are mounted in series or parallel as required. The springs are mounted in series will reduce the value of the spring constant, while the installation of spring in parallel to increase the value of the spring constant. This studyaimed toexamine thebehavior ofthe spring system, both without and with thefrictioncreatedfrictionwith the variationof mass,spring constantand theformationof differentspring system. Formationspring systemis theformation ofa simplespring systemarranged in seriesorparallel. The stage of research was conducted on the determination of the mathematical equations for the motion of the mass determined from the equilibrium position of the spring system formation include a mass spring system connected to two springs arranged series, a mass spring system connected to two springs arranged parallel and two mass spring system connected by two springs arranged series, then made a spring system simulation program. Key Words: Mass spring system, harmonik, friction, simulation.